Comparison of Efficacy of Vaginal VS Oral Prostaglandin E1 Analogue (Misoprostol) in Management of First Trimester Missed Abortion (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of misoprostol vaginally/orallyin management of first trimester missed abortion.Study Design: Quasi experimental study.Place and Duration of Study: This study was conducted at the Gynecology Department, Muhammad Medical College Hospital, Mirpurkhas from January 2013 - December 2014.Materials and Methods: Eligible women satisfying inclusion/exclusion criteria were recruited after written informed consent and given 600 µg of misoprostol vaginally/orally with a maximum of 3 doses. Patients were monitored for 24 hours following complete abortion or surgical evacuation and then discharged. The primary outcome of study was defined as Success (non surgical evacuation of product of conception) or Failure (excessive bleeding with retained product of conception where surgical evacuation was performed). Associated adverse events, patient satisfaction and acceptability to treatment were also recorded and compared. The data was analysed using SPSS version 21 (IBM, Chicago, IL).Results: Both vaginal and oral routes were highly effective, however greater proportion of patients receiving vaginal Misoprostol had success compared to those receiving oral Misoprostol (88% Vs. 71%; p-value = 0.005). Moreover, greater proportion of patients receiving vaginal Misoprostol had induction – expulsion interval within 12 hours compared to those receiving oral Misoprostol (50% vs. 39.44%; p-value = 0.041). Fewer side-effects were observed among participants receiving Vaginal Misoprostol than Oral Misoprostol. There was no significant difference in patient’s satisfaction and acceptability in participants of both groups.Conclusion: Vaginal misoprostol is more effective than oral misoprostol for first trimester missed abortion.